Environmental study of groundwater in southwest of Baghdad, Yusufiyah using GIS - Hassan, Mustafa Ali (Iraqi Journal of Physics, 2019)
Ground water hydrochemical study in Yusufiyah depends upon (25) wells where major cations and anions were obtained as well as trace elements. The hydrochemical properties include the study of (pH, EC, TDS, and TH). The groundwater of the study area is odorless and colorless except the wells (13 and 16) with a salty taste due to the elevated (TDS) concentration in it, where the wells depth ranges between 7-20 meters. Depth of water in these wells was about 25-35 meters above sea level. Groundwater generally flows from east to west and from north east to south west. The resource of groundwater depends upon surface water. Physical specifications are measured in the water samples included temperature, color, taste, odor, pH, electrical conductivity (EC) and total dissolved solids (TDS). The chemical specifications included major cations (Ca2+, Mg2+, Na+, and K+) and major anions (NO3, SO42- ,Cl-, and HCO3-) in addition to the trace elements (Fe, Ni, Co, Cd, Cu, Zn, Pb, Mn). The groundwater in the study area is polluted with some heavy elements like (Fe, Ni, Cd and Pb) because their concentrations are higher than the permissible limits according to WHO (2007) and IQS (2009).